Perturbations of O(1D) VER, Temperature, Winds, Atomic Oxygen, and TEC at High Southern Latitudes. Issue 6 (25th June 2019) - Shepherd, Marianna; Shepherd, Gordon; Codrescu, Mihail
Abstract: The study investigates previously unrecognized wind reversals of the daytime thermosphere in the Southern Hemisphere at latitudes of 50°S–70°S employing observations of O( 1 D) airglow volume emission rates (VER), temperature, and neutral winds at 170–300‐km height by the Wind Imaging Interferometer. Atomic oxygen densities derived from the Wind Imaging Interferometer O + (732–733 nm) emission observations were also considered together with contemporaneous observations of total electron content by the TOPEX Poseidon satellite mission. The O( 1 D) VER for fall equinox (March/April 1994) and summer solstice (January 1995) revealed a peak in the VER over the longitude range of 50°E–150°E, for both seasons and daytime local times. The Doppler temperatures also exhibited a maximum at the same location and times. The co‐located zonal wind field shows a westward trough at 50°E–150°E with wind speeds reaching −450 m/s and an eastward peak at 200°E–300°E. Meridional winds show a "peak and trough" structure over the 50°E–150°E region, with a distinct eastern boundary at 150°E. During summer solstice the atomic oxygen is depleted at the region of the O( 1 D) VER enhancement in the presence of westward zonal wind. However, the total electron content observations showed a peak that coincided with the O( 1 D) VER and temperature enhancements. Plain Language Summary: The study investigates unusual perturbations in upper atmospheric winds that occur at a very specific location in the high‐latitude Southern Hemisphere. These include wind reversals, enhancements in the "red line" atomic oxygen airglow emission at 630.0 nm, temperature, depletion of atomic oxygen, and enhancements of ionospheric electron density. The location is 50°E–150°E longitude, 50°S–70°S latitude. The atmospheric observations were made by the Wind Imaging Interferometer, launched on NASA's Upper Atmosphere Research Satellite in 1991; these continued until 2003. The wind reversals involved westward winds of as strong as 450 m/s. The electron densities were of total electron content integrated along the line of sight from the satellite to the Earth and were obtained from the TOPEX satellite for the same time periods as the Wind Imaging Interferometer observations. Measurements were made at equinox and summer solstice and the atmospheric observations were the same for both. These new observations point the way to future studies of this highly localized phenomenon. Key Points: Previously unrecognized perturbations in thermospheric and ionospheric winds are observed at a specific high latitude location, 50°E–150°E and at 50°S–70°S The neutral winds show a reversal to westward reaching −450 m/s, with a peak and trough structure of meridional wind, having an eastern boundary at 150°E Enhancements occur in daytime O( 1 D) emission, temperature, and TEC; atomic oxygen is depleted